María Eugenia Dengo Obregón: mujer de lectura, educación y cultura... - Eduarte Salazar, José Pablo (2008)
The article is a biographical sketch of the Licda. Maria Eugenia Dengo Obregón widow of Vargas, who crosses their life and works in their personal facet, professional, public and, more recently, like exponent of the Costa Rican culture. It is a tribute to the figure of this untiring woman, who with her reading and writing has managed to leave a legacy in the Costa Rican education, like professor, Dean, Vicerectora, Minister and ex- Minister of Public Education of Costa Rica. The Licda. Dengo Obregón was awarded with the National Prize of Culture â€œMagón 2007â€, granted by the Ministry of Culture and Youth of the Republic from Costa Rica to its 82 years of age. â€œHonor to which honor deservesâ€.